2022
DOI: 10.3390/ma15082803
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of β-Chitin Extraction Byproduct from Cuttlefish Bone and Its Application in Food Wastewater Treatment

Abstract: The nontoxicity, worldwide availability and low production cost of cuttlefish bone products qualify them an excellent biocoagulant to treat food industry wastewater. In this study, cuttlefish bone liquid waste from the deproteinization step was used as a biocoagulant to treat food industry wastewater. This work concerns a waste that has never before been investigated. The objectives of this work were: the recovery of waste resulting from cuttlefish bone deproteinization, the replacementof chemical coagulants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…For instance, chitosan from cephalopod waste proved effective in removing cadmium (Cd) from aqueous solutions, with optimal conditions at pH 7, 42.5 • C, 220 min, and 1 g/L sorbent dosage (Kavisri et al, 2023), highlighting the role of surface pores in adsorption. Nouj et al (2022) demonstrated that β-chitin from cuttlefish bone significantly reduced turbidity, BOD, and COD in food processing wastewater. Similarly, Siswoyo et al (2023) found that chitosan from blood cockle shells reduced total suspended solids and turbidity in well-water.…”
Section: Food Industrial Applicationmentioning
confidence: 99%
See 3 more Smart Citations
“…For instance, chitosan from cephalopod waste proved effective in removing cadmium (Cd) from aqueous solutions, with optimal conditions at pH 7, 42.5 • C, 220 min, and 1 g/L sorbent dosage (Kavisri et al, 2023), highlighting the role of surface pores in adsorption. Nouj et al (2022) demonstrated that β-chitin from cuttlefish bone significantly reduced turbidity, BOD, and COD in food processing wastewater. Similarly, Siswoyo et al (2023) found that chitosan from blood cockle shells reduced total suspended solids and turbidity in well-water.…”
Section: Food Industrial Applicationmentioning
confidence: 99%
“…Nouj et al. (2022) demonstrated that β‐chitin from cuttlefish bone significantly reduced turbidity, BOD, and COD in food processing wastewater. Similarly, Siswoyo et al.…”
Section: Food Industrial Applicationmentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6][7][8] In the last few years, numerous scientific papers have been published with the aim of finding solutions to this environmental contamination problem. [9][10][11][12][13][14][15][16] Despite this vast scientific production, researchers in the field are still not satisfied with the results. 17,18 Further, several solutions were proposed aiming to improve either the process or the material used in the polluted water treatment.…”
Section: Introductionmentioning
confidence: 99%